Sub-Irrigated Alfalfa Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S.; Martin, Kent L. (My University, 2010)
This publication contains information for a projected budged reflecting expected income and cost based on sub-irrigated alfalfa production practices in western Kansas.
MF2367_2010_11
Keywords: MF2367; Economics; Crops; MF